2009
DOI: 10.1111/j.1742-4658.2009.07452.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1‐inducible MCPIP protein has structural and functional properties of RNase and participates in degradation of IL‐1β mRNA

Abstract: In human monocyte‐derived macrophages, the MCPIP gene (monocyte chemoattractant protein‐induced protein) is strongly activated by interleukin‐1β (IL‐1β). Using bioinformatics, a PIN domain was identified, spanning amino acids 130‐280; such domains are known to possess structural features of RNases. Recently, RNase properties of MCPIP were confirmed on transcripts coding for interleukins IL‐6 and IL‐12p40. Here we present evidence that siRNA‐mediated inhibition of the MCPIP gene expression increases the level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
200
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(216 citation statements)
references
References 28 publications
13
200
0
3
Order By: Relevance
“…Only a handful of bona fide mRNA endonucleases have been identified (Tomecki and Dziembowski 2010;Schoenberg 2011;Schoenberg and Maquat 2012). These are PMR1 , ZC3H12A (also called MCPIP1) (Matsushita et al 2009;Mizgalska et al 2009), APE1 (Barnes et al 2009), SMG6 (Huntzinger et al 2008;Eberle et al 2009), and IRE1 (Han et al 2009;Hollien et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Only a handful of bona fide mRNA endonucleases have been identified (Tomecki and Dziembowski 2010;Schoenberg 2011;Schoenberg and Maquat 2012). These are PMR1 , ZC3H12A (also called MCPIP1) (Matsushita et al 2009;Mizgalska et al 2009), APE1 (Barnes et al 2009), SMG6 (Huntzinger et al 2008;Eberle et al 2009), and IRE1 (Han et al 2009;Hollien et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has also been found in other CCCH zinc-finger-containing proteins such as tristetraprolin (TTP) and Roquin (Taylor et al, 1996;Vinuesa et al, 2005;Yu et al, 2007). Recently, numerous studies have focused on the RNase activity of MCPIP1 targeting on the mRNAs of IL-6, IL-1β (Matsushita et al, 2009;Mizgalska et al, 2009), and pre-microRNAs (Suzuki et al, 2011). Another study shows that MCPIP1 can act as a deubiquitinating enzyme (DUB) targeting TNF receptor-associated factor (TRAF) family proteins (Liang et al, 2010).…”
Section: Introductionmentioning
confidence: 73%
“…However, Matsushita et al (Matsushita et al, 2009) has later found that MCPIP1 is in the cytoplasm fraction rather than in the nuclear extract. Further investigation also reveals that MCPIP1 is localized in the cytoskeleton fraction, and some other proteins involved in mRNA metabolism have the same localization in cells (Henics, 1999;Mizgalska et al, 2009). More evidence is needed to prove the transcription factor activity of MCPIP1.…”
Section: Transcription Factormentioning
confidence: 89%
“…This last protein (HuR) acts in a rather unusual way since it stabilizes mRNA and prolongs its life in the cell. On the other hand, macrophage chemotactic protein-induced protein-1 (MCPIP1), studied also in our laboratory Skalniak et al, 2009), is able to degrade mRNAs coding for IL-1 , IL-6 and IL-12p40 (but not for TNFalpha), although it does not require the ARE signal (Matsushita et al, 2009;Mizgalska et al, 2009)  Finally, the majority of proteins involved in the control of inflammatory response exhibit short half-lives being susceptible to degradation in a proteasome after initial ubiquitination (for references see Evans, 2005). This variable length of life and a fast turnover of mediators of inflammation, achieved either at the stage of their mRNA or mature protein, permit for elastic control and fine regulation of inflammatory reactions.…”
mentioning
confidence: 99%